IMPROVING THE SYSTEM FOR USING GEOINFORMATION TECHNOLOGIES IN MONITORING PASTURE LANDS (IN THE EXAMPLE OF VOBKENT DISTRICT) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In this article, the geoinformation technology system allows you to monitor the condition, quantity and effective use of pasture lands. Geographic information system technologies allow you to simultaneously monitor many areas, determine their condition, increase their efficiency, and implement preventive measures. It is possible to monitor pastures through space and aerial photographs, determine their condition and implement the necessary measures, and by observing the expansion or contraction of pastures, it is possible to determine the results of the measures taken by comparing annual reports and annual results over the years. With this information, it is possible to effectively use pastures and improve their condition. Pasture lands also play an important role in the production of food in livestock farming.
Keywords: Geoinformation technologies, preventive measures, space and aerial photographs, information about pasture lands.